Towards A Pedagogy for Disempowering Our Enemies - Ian Baptiste (Adult Education Research Conference, 1998)
Adult educators seem hesitant to disempower anyone, including their enemies. This is because our humanist moorings makes us believe that all forms of disempowerment is evil. Proposed are rudiments of a pedagogy of ethical disempowerment, which I contend we desperately need.